Functionalized UiO-66-NH2 by trimellitic acid for highly selective adsorption of basic blue 3 from aqueous solutions - Wang, Tingting; Han, Lin; Li, Xin; Chen, Tianen; Wang, Shifeng (Frontiers in Chemistry, 2022)
Abstract A novel metal-organic framework (MOF), UiO-66-TLA was synthesized effectively remove the basic dye basic blue 3 (BB3) from wastewater using trimellitic acid as a modifier. Modification with carboxyl groups facilitates the adsorption of the cationic dye Basic Blue 3. The adsorption of BB3 by the modified UiO-66-TLA was significantly greater than that of its parent MOF. The adsorption capacity of the modified UiO-66-TLA for BB3 (234.23 mg/g) was 93.2% higher than that of the original UiO-66-NH2 (121.24 mg/g). UiO-66-TLA was successfully synthesized as indicated by various characterization results. The adsorption kinetics conformed to the pseudo-second-order model, and the adsorption isotherm conformed to the Redlich-Peterson isotherm. This indicates that BB3 is a multi-parameter model of monolayer/multilayer arrangement on the adsorbent surface, and its rate-controlling step is chemisorption. The thermodynamic results show that the adsorption process was non-spontaneous and belonged to an endothermic reaction. The interaction of the modified UiO-66-TLA with BB3 was mainly affected by mechanisms, such as electrostatic interaction and π–π stacking. These results demonstrate that UIO-66-TLA is an effective material for the efficient and selective removal of BB3 in solution, which is of practical interest.